Justification inclusion of physiotherapy and self-reflexotherapy program physical rehabilitation of adolescents with short-sightedness - Redkovets, T.G.; Romman, Haytham J.M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : To substantiate the combined use of therapeutic exercises and Onnuri therapy to restore vision in teenagers with myopia. Material: analysis of more than 80 sources of literature on the subject to study the prevalence of myopia in adolescents and the impact of physical rehabilitation for restoration of view. Results : It was established that the increase in the prevalence of myopia in adolescents with greater visual load, requires the development of new approaches to rehabilitation. Data on the impact kinesotherapy and reflexology on the body. Presents the rationale of their use in rehabilitation, with the principles of conduct, with myopia. Conclusions : kinesis therapy, compliance with recommendations for the application of different directivity exercises limited power voltage, over- load of a physical and jumping, should be combined with the methods of self-reflection therapy (self-massage, application of seed, color effects) for more high effect of restoring vision.